Fertility preservation in women harboring deleterious BRCA mutations: ready for prime time?. Issue 2 (1st December 2017) - Peccatori, Fedro Alessandro; Mangili, Giorgia; Bergamini, Alice; Filippi, Francesca; Martinelli, Fabio; Ferrari, Federica; Noli, Stefania; Rabaiotti, Emanuela; Candiani, Massimo; Somigliana, Edgardo
Abstract: Fertility issues have become critical in the management and counseling of BRCA mutation carriers. In this setting four points deserve consideration. (1) Women in general lose their ability to conceive at a mean age of 41 years, thus the suggested policy of prophylactic bilateral salpingo-oophorectomy at age 40 for BRCA mutation carriers does not affect the chances of natural pregnancy. Conversely, if the procedure is chosen at 35 years old, oocyte cryopreservation prior to surgery should be considered. (2) Some evidence suggests that ovarian reserve may actually be partly reduced in BRCA mutations carriers and that the mutation may affect ovarian responsiveness to stimulation. However, these findings are still controversial. (3) Breast cancer is not rare before the age of 40 and fertility preservation after diagnosis can be requested in a significant proportion of BRCA mutation carriers. Thus, a policy of oocyte cryopreservation in young healthy carriers deserves consideration. The procedure could be considered at a young age and in an elective setting, when ovarian stimulation may yield more oocytes of better quality. (4) Preimplantation genetic diagnosis (PGD) could be considered in BRCA mutations carriers, particularly when good quality oocytes have been stored at a young age. Based on the current knowledge, a univocal approach cannot be recommended; in depth patient counseling is warranted.